Patu Mbojo: Sastra Lisan Bima dalam Kajian Stilistika: Patu Mbojo: Bima Oral Literature in Stylistic Studies - Meilani Putri, Rahmin (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
This research discusses the language style in patu mbojo. Because the whole poem is the content (it does not have a cover like pantun in general), patu becomes a medium of communication that is quite dense in meaning in the process of achievement. The data in this study consisted of eight parts chanted by two speakers, male and female. The purpose of this study is to find and identify the number of language styles used in the whole poem. The qualitative method is considered appropriate for this research and applies the method of listening and recording with descriptive analysis. The study used in this research is stylistic study. The language styles found in patu mbojo are divided into four, namely based on the selection of words, tone (the medium language style in patu mbojo aims to create a happy and peaceful atmosphere, so the tone contains humor or something fun), sentences (climax, anticlimax, parallelism, and repetition; anaphora and mesodiplosis), and directness of meaning (rhetorical; alliteration, assonance, apophasis or preterition, pleonasm, silepsis, hyperbole, and paradox and figurative language styles; simile, antonomasia, sarcasm, and pun or paranomation). Overall, the language style used is a conversational language style that is rich in various kinds of allusions to beautify and sharpen the meaning in the overall content of the poem.